Influence of bioturbation by Hediste diversicolor on mercury fluxes from estuarine sediments: A mesocosms laboratory experiment - Cardoso, P. G. (2008)
Mercury, with its reactive forms being the most deleterious for the trophic chains, has been identified as a major pollutant in a few confined bodies of the coastal zone. Due to feeding, burrowing, and bioirrigation activities, infauna are known to play a crucial role in the biogeochemical processes of contaminants. The main goal of the present study is to evaluate the effects of Hediste diversicolor bioturbation on mercury fluxes from estuarine sediments in a mesocosms laboratory experiment. Additionally, an attempt was made to establish a relationship between the amount of remobilised mercury to the water column and the degree of contamination of the sediments using a mercury contamination gradient.